Modern approaches for the detection and prediction of invasive pests - Vishwajeet; Kumar, Anil; Kumar, Navnit; Rana, Lalita; Singh, S N; Singh, A K (Indian Farming, 2023)
The accelerated pace of commercial and social globalization has created opportunities for the movement of species to new areas of the world. As arthropods are dispersed beyond their native ranges, they escape population-regulating predators, parasitoids and pathogens and encounter naive host plants and animals. In absence of these regulating factors, they find opportunity in almost logarithmic fashion. In the past, we have examples of many successful invasion which have caused havoc on environment. With the advancement of technology in the current scenario, we need to imply these technologies in the field of invasion science. With regards to invasion of a species, early detection of the pest is the most lauded approach to address invasive alien species. For the early detection, technologies such as x-ray technique, acoustics, volatile chemical profile, genetic approaches and geographic information system (GIS) can be incorporated.